Coordinated control of volume regulatory Na(+)/H(+) and K(+)/H(+) exchange pathways in Amphiuma red blood cells - Ortiz-Acevedo, Alejandro (American Physiological Society, 2010)
The Na(+)/H(+) and K(+)/H(+) exchange pathways of Amphiuma tridactylum red blood cells (RBCs) are quiescent at normal resting cell volume yet are selectively activated in response to cell shrinkage and swelling, respectively. These alkali metal/H(+) exchangers are activated by net kinase activity and deactivated by net phosphatase activity. We employed relaxation kinetic analyses to gain insight into the basis for coordinated control of these volume regulatory ion flux pathways. This approach enabled us to develop a model explaining how phosphorylation/dephosphorylation-dependent events control and coordinate the activity of the Na(+)/H(+) and K(+)/H(+) exchangers around the cell volume set point. We found that the transition between initial and final steady state for both activation and deactivation of the volume-induced Na(+)/H(+) and K(+)/H(+) exchange pathways in Amphiuma RBCs proceed as a single exponential function of time. The rate of Na(+)/H(+) exchange activation increases with cell shrinkage, whereas the rate of Na(+)/H(+) exchange deactivation increases as preshrunken cells are progressively swollen. Similarly, the rate of K(+)/H(+) exchange activation increases with cell swelling, whereas the rate of K(+)/H(+) exchange deactivation increases as preswollen cells are progressively shrunken. We propose a model in which the activities of the controlling kinases and phosphatases are volume sensitive and reciprocally regulated. Briefly, the activity of each kinase-phosphatase pair is reciprocally related, as a function of volume, and the volume sensitivities of kinases and phosphatases controlling K(+)/H(+) exchange are reciprocally related to those controlling Na(+)/H(+) exchange.